Membangun UMKM dengan Identitas Budaya Batik Melalui Kerajinan Tas Kulit di Lingkungan XXIX Kelurahan Rengas Pulau Kecamatan Medan Marelan Kabupaten Kota Medan - Farsya Zuhra (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
This Independent Community Service Program (KKN) was implemented by students of the Muhammadiyah University of North Sumatra in Lingkungan XXIX, Rengas Pulau Village, Medan Marelan District. This activity focuses on empowering micro, small and medium enterprises (MSMEs) through the application of batik cultural identity to leather bag crafts. Through this service, students help local craftsmen to combine batik motifs with leather bags in order to increase the aesthetic value and selling power of the product. The main objective of this activity is to increase public awareness of the importance of maintaining and preserving national cultural heritage, especially batik, as well as to provide education to craftsmen regarding the application of traditional techniques in leather bag production. This program consists of several activities, including training in making batik leather bags, socializing early savings in schools, and mutual cooperation activities to maintain environmental cleanliness. The results of this activity show an increase in the knowledge and skills of craftsmen in producing culturally valuable products, as well as increasing community participation in MSME activities. In addition, students also succeeded in motivating residents to be more active in protecting the environment and increasing awareness of the importance of health through integrated health service post activities. Thus, this KKN not only contributes to the development of the local economy, but also to the preservation of culture and improving community welfare.